The Catalytic Role of RuBisCO for in situ CO2 Recycling in Escherichia coli - Pang, Ju-Jiun; Shin, Jong-Shik; Li, Si-Yu (Frontiers in Bioengineering and Biotechnology, 2020)
Ribulose-1,5-bisphosphate carboxylase/oxygenase (RuBisCO) is a key enzyme responsible for biological CO2 assimilation. RuBisCO can be heterologously expressed in Escherichia coli so that glucose and CO2 are co-metabolized to achieve high mixotrophic metabolite production, where the theoretical yield of mixotrophic metabolite production is 2.4 mol(ethanol+acetate+pyruvate)/molglucose. However, RuBisCO is known for its low kcat and forming inhibited complexes with its substrate ribulose-1,5-bisphosphate (RuBP) and other sugar phosphates, yet the inhibited form of RuBisCO can be reversed by RuBisCO activase (Rca). In this study, RuBisCO forms I and II were cloned and expressed in Escherichia coli for in situ CO2 recycling, where CO2 produced during glucose fermentation was recycled and in vivo co-metabolized with the glucose. In addition, forms I and II RuBisCO activases were co-expressed with RuBisCO in E. coli to determine their in vivo effects on in situ CO2 recycling. Form I RuBisCO activase (Rca1) was co-expressed with form I RuBisCO and form II RuBisCO activase (Rca2) was co-expressed with form II RuBisCO. The results showed that both form I and form II RuBisCO’s exhibit comparable activities in E. coli and generated similar levels of in situ CO2 recycling. A significant increase in the total metabolite yield from 1.5±0.1 to 2.2±0.1 mol(ethanol+acetate+pyruvate)/molglucose occurred when Rca2 was co-expressed with form II RuBisCO. Meanwhile, the total metabolite yield increased from 1.7±0.1 to 2.0±0.1 mol(ethanol+acetate+pyruvate)/molglucose when Rca1 was co-expressed with form I RuBisCO. This data suggests that both forms I and II RuBisCO are subject to in vivo RuBP inhibition yet can be relieved by the co-expression of Rca. Interestingly, it is suggested that the in vivo RuBP inhibition of form II RuBisCO can be more easily reversed compared to form I. When the catalytic power of RuBisCO is maintained by Rca, the high activity of phosphoribulokinase (Prk) plays an important role in directing glucose to the RuBisCO-based engineered pathway and fermentation yields of 2.1-2.3 mol(ethanol+acetate+pyruvate)/molglucose can be obtained. This study is the first to demonstrate that in vivo RuBP inhibition of RuBisCO can be a bottleneck for in situ CO2 recycling in E. coli.